Design and joining of graphite to copper by a simple direct casting technology. (1st January 2011) - Zhou, Zhangjian; Zhong, Zhihong; Qu, Dandan; Ge, Changchun
A simple low-cost direct casting technology has been developed for joining graphite and copper. The direct casting of copper on graphite was possible through mixing transition metal (Cr) powders with Cu powders to decrease the contact angle between graphite and copper and form a carbide layer at high temperature (>1100°C) in a vacuum furnace for 20–80 min. For decreasing the coefficient of thermal expansion of copper alloy, refractory metal W powders were also added into the mixed powders. The reaction between the transition metal and graphite determined the formation of a thin carbide layer on the graphite surface, as detected by X-ray diffraction analysis. The cross-section of the joined samples was observed by SEM. The shear strength of the C-Cu joints was measured at room temperature with a compression machine.